Superelastic and ultralight electron source from modifying 3D reduced graphene aerogel microstructure. (March 2017) - Yang, Congxing; Liu, Nishuang; Zeng, Wei; Long, Fei; Song, Zengcai; Su, Jun; Li, Luying; Zou, Zhengguang; Fang, Guojia; Xiong, Lun; Gao, Yihua
Abstract: Electron sources (ES) are an essential tool in flexible field emitters (FEs). However, in special desired environment conditions, the elastic and ultralight FEs with outstanding field emission performance are desired due to the limitation of traditional ES. Here we report a superelastic and ultralight ES based on 3D graphene aerogel (rGA) with growing Ag nanoparticles (rGA@Ag) or carbon nanotubes (rGA@CNTs) on graphene sheets to optimize the field emissions performance by a simple and environmentally friendly method. The 3D rGA show its advantages for ES. Its special structure endows the ultralight and compressibility. The rGA@Ag and rGA@CNTs have low values of turn-on field of 1.35 V μm −1 and 0.87 V μm −1, respectively. The rGA@CNTs have a high enhancement factor (~8204), an excellent emission stability (fluctuation ~15%), and a field emission performance enhanced instead of weakened by compression. The ES from rGA@Ag and rGA@CNTs can reach a 98% compression and return to initial state without shrink. Both experiment and simulation demonstrate that the field emission performance is enhanced by compression. The ultralight ES can stand on stamens of peach blossom without curvature deformation. The unique structure of the rGA and its new application will open a routine to elastic and ultralight ES. Graphical abstract: Highlights: The special fence frame structure of 3D rGA increases the emitter aspect ratio and enhances the field emission performance. Modification on the rGA by growing Ag and CNTs nanomaterials is an effective way to improve field emission performance. The field emission performance of electron sources was enhanced during compressing due to the weaker screening effect.